Structure and post-translational modifications of the web silk protein spidroin-1 from Nephila spiders - Aparecido dos Santos-Pinto, Jose Roberto [UNESP]; Lamprecht, Guenther; Chen, Wei-Qiang; Heo, Seok; Hardy, John George; Priewalder, Helga; Scheibel, Thomas Rainer; Palma, Mario Sergio [UNESP]; Lubec, Gert (Elsevier B.V., 2014)
Spidroin-1 is one of the major ampullate silk proteins produced by spiders for use in the construction of the frame and radii of orb webs, and as a dragline to escape from predators. Only partial sequences of spidroin-1 produced by Nephila clavipes have been reported up to now, and there is no information on post-translational modifications (PTMs). A gel-based mass spectrometry strategy with ETD and CID fragmentation methods were used to sequence and determine the presence/location of any PTMs on the spidroin-1. Sequence coverage of 98.06%, 95.05%, and 98.37% were obtained for N. clavipes, Nephila edulis and for Nephila madagascariensis, respectively. Phosphorylation was the major PTM observed with 8 phosphorylation sites considered reliable on spidroin-1 produced by N. clavipes, 4 in N. madagascariensis and 2 for N. edulis. Dityrosine and 3,4-dihydroxyphenylalanine (formed by oxidation of the spidroin-1) were observed, although the mechanism by which they are formed (i.e. exposure to UV radiation or to peroxidases in the major ampullate silk gland) is uncertain. Herein we present structural information on the spidroin-1 produced by three different Nephila species; these findings may be valuable for understanding the physicochemical properties of the silk proteins and moreover, future designs of recombinantly produced spider silk proteins.Biotechnological significanceThe present investigation shows for the first time spidroin structure and post-translational modifications observed on the major ampullate silk spidroin-1. The many site specific phosphorylations (localized within the structural motifs) along with the probably photoinduction of hydroxylations may be relevant for scientists in material science, biology, biochemistry and environmental scientists. Up to now all the mechanical properties of the spidroin have been characterized without any consideration about the existence of PTMs in the sequence of spidroins. Thus, these findings for major ampullate silk spidroin-1 from Nephila spiders provide the basis for mechanical-elastic property studies of silk for biotechnological and biomedical potential applications.This article is part of a Special Issue entitled: Proteomics of non-model organisms. (C) 2014 Published by Elsevier B.V.
Keywords: Proteomic analysis; Mass spectrometry; Peptide sequencing; Phosphorylation; Dityrosine